PELATIHAN PEMBUATAN MINUMAN DARI TANAMAN EMPON-EMPON PADA KULIAH KERJA NYATA DARI RUMAH DI KELURAHAN TAMANAN KEC. MOJOROTO KOTA KEDIRI - M. Jamalun Nizar; Ervin Arifudin (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2022)
This article aims to innovate and use empon-empon as a booster for citizens' immunity from the Covid-19 virus. Where this activity was carried out during KKN-DR during the pandemic. The KKN-DR model uses the PAR (Participatory Action Research) method. PAR has three key variables namely, Participatory, Action (action) and Research (research). The results of the activity stated that KKN-DR which is oriented towards increasing the potential of students where they live can be carried out well. The focus of KKN-DR is on socializing the prevention and anticipation of Covid-19, as well as making herbal drinks made from empon-empon. There are advantages and disadvantages in carrying out the KKN DR program activities that have been carried out in carrying out these KKN DR activities. As a recommendation, it is necessary to increase the understanding and importance of the toga plant as a preventive measure for all forms of minor ailments. Given its massive availability in several places.